2013
DOI: 10.1590/s1984-82502013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of CFC free inhalers for beclomethasone dipropionate

Abstract: Beclomethasone dipropionate CFC free inhalation formulations were developed with a view to treat asthma prophylactically. Dry powder inhalers (DPI) for beclomethasone dipropionate were prepared with different grades of lactose monohydrate. The influence of carrier and overages on performance of DPI was studied. Metered dose inhalers (MDI) with HFA based propellants were formulated with various doses, overages and different concentrations of alcohol. Formulated DPI and MDI were evaluated for various official an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…All play roles in the formation of the aerosol cloud and delivery efficiency (Smyth, 2003; Newman, 2005). They mainly depend on using different types of propellants but recently, hydrofluroalkane (HFA) propellant-based MDI formulations were developed to be used instead of chlorofluorocarbons (CFC) propellants-based formulations which were banned since 1996 as they were reported to destroy the ozone layer (Talasila et al., 2013). MDI formulations are prepared either by dissolving the drug into the HFA (such as HFA 134a and HFA 227) if it has sufficient solubility in the HFA, or using a co-solvent, usually ethanol, to increase the solubility of the drug in the HFA.…”
Section: Introductionmentioning
confidence: 99%
“…All play roles in the formation of the aerosol cloud and delivery efficiency (Smyth, 2003; Newman, 2005). They mainly depend on using different types of propellants but recently, hydrofluroalkane (HFA) propellant-based MDI formulations were developed to be used instead of chlorofluorocarbons (CFC) propellants-based formulations which were banned since 1996 as they were reported to destroy the ozone layer (Talasila et al., 2013). MDI formulations are prepared either by dissolving the drug into the HFA (such as HFA 134a and HFA 227) if it has sufficient solubility in the HFA, or using a co-solvent, usually ethanol, to increase the solubility of the drug in the HFA.…”
Section: Introductionmentioning
confidence: 99%
“…There was a linear correlation between total actuation, hypothetical actuation and manufacturer recommended actuation.The correlation is strongest between total actuation and hypothetical actuation (r=0.995, p<0.001) compared to manufacturer-recommended actuation and hypothetical actuation(r=0.970, p<0.001). This nding suggests that each canister could be actuated past manufacturer's recommendation similar with a study by Talasila 3 to investigate the effect of extra actuation on dose delivery showed that canister should be packaged with extra actuation of 15-30% to deliver the required 200 metered dose as marketed by manufacturer. Table 4 compared the mean weights of the Salbutamol (GSK) obtained from a study done in European country 10 with our nding.…”
Section: Methodsmentioning
confidence: 74%
“…After crimping and filling, the canisters were sonicated in a water bath containing cool water at 10°C for 15 minutes to check for any leakage and to ensure homogenous mixing of the contents, affix/installed the canister in Autohaler. [9][10][11]…”
Section: Formulations Preparation Methodsmentioning
confidence: 99%